Women from Venus, men from Mars: inter-sex foraging differences in the imperial cormorant Phalacrocorax atriceps a colonial seabird - Rory Wilson (Oikos, 2011)
Quintana, F., Wilson, R. P., Dell’Arciprete, P., Shepard, E. L. C., Gómez Laich, A. (2010). Women from Venus, men from Mars: inter-sex foraging differences in the imperial cormorant Phalacrocorax atriceps a colonial seabird. Oikos (in press).